Assessment of Left Ventricular Dysfunction Post Transcatheter Patent Ductus Arteriosus Closure in Pediatric Patients - Babar, Muhammad Waleed (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To compare Left Ventricular (LV) function before and after Transcatheter Patent Ductus Arteriosus (PDA) closure and to identify factors associated with LV dysfunction following device closure. Study Design: Quasi- experimental study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, Jan to Jun 2024. Methodology: A non-probability consecutive sampling technique was used for patient selection. Thirty patients aged upto 18 years who underwent PDA device closure were enrolled. Echocardiographic parameters were measured before, 24 hours after device closure and at 1 and 3 months. Assessment of pre procedure LV function was done upon admission of the patient and the parameters were recorded in predesigned profoma using M mode echocardiography, TDI and Speckled tracking. Trans catheter device closure of PDA was done using standard procedure and following the standard guidelines. Results: Out of 30 patients, 17(56.7%) were males and 13(43.3%) were females. The median age of patients was 4.00(2.75-6.00) year. After 24 hours of procedure, 5(16.7 %) patients developed LV dysfunction. Patients with LV dysfunction had a median PDA diameter of 8.00(8.00-9.00) mm. LAd/AOd ratio 1.24(1.22-1.32) was significantly higher in patients with LV dysfunction (p<0.05). The LAd, LVEDD, LVESD and LVEDVI showed a significant decline following procedure and throughout the course of 3 months (p<0.001). Conclusions: Transcatheter PDA closure causes a decrease in LV performance immediately post procedural closure, which recovers completely within 3 months. Pre closure LAd/Aod ratio and PDA diameter were found to be an important markers in anticipating LV dysfunction ...